The role of D-dimer in diagnosis of cerebral sinus venous thrombosis - Farahmand Sadr, Maryam; Fadakar, Nima; Mansuri Mehrabadi, Susan; Zolghadrasli, Yasaman; Poursadeghfard, Maryam (Archives of Medical Laboratory Sciences, 2020)
Background: Cerebral sinus venous thrombosis (CSVT) is a fatal condition and should be considered in all patients with acute new onset headache. D-dimer has been shown to be a sensitive diagnostic tool in deep vein thrombosis and pulmonary thromboembolism. The purpose of this study was to investigate whether this test could be useful in the diagnosis of CSVT. Methods: In this prospective study, we reviewed patients referring to Nemazee hospital with presentations suggestive of CSVT. Diagnosis was established, using MRI and MRV. Serum D-dimer level was checked among 24 hours after hospital admission. Results: From 117 enrolled patients, 37 (31.6%) patients had CSVT. The reported D-dimer levels showed negative (< 500 ng/ml) in 21 (56.76%) and positive level in 16 (43.24 %) patients who had CSVT. Also, D-dimer was negative in 66 (82.5%) and positive in 14 (17.5%) patients who did not have CSVT. These results demonstrated a sensitivity of 43.24%, specificity of 82.5%, positive predictive value of 53.3%, and negative predictive value of 75.86%. Conclusion: Normal D-dimer levels make the presence of CSVT very unlikely; our study suggests that D-dimer test may guide us to approach patients who are suspected with CSVT in emergency situations with limited access to MRI/MRV. However, every patient with D-dimer level more than 500 ng/mL and high clinical suspicion of CSVT should undergo MRI/MRV. In addition, our results showed a negative D-dimer test was not a reliable assay to completely rule out CSVT. However, we recommend further studies to confirm our results.